Pulmonary function in tropical eosinophilia - Nesarajah, M. S. (1972)
Pulmonary function studies were carried out on 23 patients with tropical eosinophilia. These showed an obstructive ventilatory defect in patients with symptoms for less than one month, and a restrictive ventilatory defect in addition to obstruction in those with symptoms for one to four months. These findings are correlated with the pathological changes observed by other workers in patients suffering from tropical eosinophilia.